Mejoramiento del proceso de producción y optimización de agregados producidos en el quebrador Las Flores del Chirripó - Araya-Vargas, Erick Alberto (Instituto Tecnológico de Costa Rica, 2010)
Different solutions are presented to improve the quality of concrete aggregates, which are generated in the production process in Constructora Navarro breaker, based on mobile equipment that allow the transfer to any place that is required. The study was prepared specifically for the company located in Río Frío Sarapiquí, on the block "Las Flores Del Chirripó" the one located in a concession over the Sucio river. The quality of the study is based on the materials characterization by ASTM standards, compared to the specifications of the 10854 MEIC regulations of concrete aggregates. Different alternative scenarios are taken into account for improving production in the breaker "Las Flores", searching for previous survey of the site layout, after that, costs by hour of machinery and performance data taken in place were determined for establishing the actual cost per cubic meter of material produced. The results illustrated that there are deficiencies in the quality of aggregates and the current distribution of the actual place is not the most appropriate to facilitate and make the production efficient.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Concreto; Análisis de costos; Especificaciones; Normativa; Mejora continua